2012
DOI: 10.1177/1077695811428885
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the Core of Journalism Education

Abstract: To carry out their mission of preparing students to be successful journalism professionals, educators make important decisions on the core curriculum: the common courses that all journalism students must take to graduate, no matter their area of emphasis or academic constraints. This national study of U.S. journalism program directors shows they agreed that training in writing and reporting is still considered the bedrock of journalism and that knowledge about visual communication has become an increasing prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 12 publications
0
14
0
2
Order By: Relevance
“…In such a curriculum, students are taught how to "create an integrated media product, one which combines elements of both print and broadcast within a digital environment" (Kraeplin & Criado, 2005, p. 54). Results of a case study examination of the Tampa News Center by Dupagne and Garrison (2006) and studies by Owens (2012, 2013) and by Blom and Davenport (2012) support the need for traditional and new skills for success in the current job market. Respondents to Dupagne and Garrison's (2006) study agreed that graduates should be familiar with multimedia; however, "good communication, reporting, and writing skills remain the bedrock of the news profession" (p. 251).…”
Section: Literature Reviewmentioning
confidence: 88%
“…In such a curriculum, students are taught how to "create an integrated media product, one which combines elements of both print and broadcast within a digital environment" (Kraeplin & Criado, 2005, p. 54). Results of a case study examination of the Tampa News Center by Dupagne and Garrison (2006) and studies by Owens (2012, 2013) and by Blom and Davenport (2012) support the need for traditional and new skills for success in the current job market. Respondents to Dupagne and Garrison's (2006) study agreed that graduates should be familiar with multimedia; however, "good communication, reporting, and writing skills remain the bedrock of the news profession" (p. 251).…”
Section: Literature Reviewmentioning
confidence: 88%
“…Similarly, Russial and Santana (2011) report that not all journalists are expected by employers to master crossplatform skills, but that basic skills, specialization, and adaptive expertise are equally valued. Journalism directors in the U.S. mostly agree that reporting and writing courses are essential and that a focus on visual communication is more important than ever, but they otherwise vary widely in their opinions about what courses should be part of a core journalism program (Blom and Davenport, 2012). There is also evidence that journalism students should learn mass communication theoretical knowledge if they want to evolve with the industry (Carpenter, 2009).…”
Section: Balancing Journalistic Skills and Specialized Knowledgementioning
confidence: 99%
“…However, Blom and Davenport found that program directors in journalism education didn't rank entrepreneurial journalism or media management or media economics as part of their seven most important core courses. 12 Entrepreneurial journalism ranked higher than did media economics, garnering 11 percent of respondents; media economics received 7 percent, while media management received 6 percent. Media ethics and law, reporting (gathering and storytelling), multimedia and storytelling, writing across the media, reporting (news gathering), visual communication and feature writing were selected by a higher percentage of respondents.…”
mentioning
confidence: 98%
“…9 Blom and Davenport report that a number of studies have concluded journalists and educators have different priorities, but indicate there is considerable agreement on certain content areas. 10 This consensus is most visible within the undergraduate curriculum, where journalism and mass communication programs are focused on skills that prepare students for entry-level careers in legacy media.…”
mentioning
confidence: 99%